Stakeholder Collaboration to Develop an Evaluation Tool to Assess the Accessibility of Cultural Institutions for Families With Children With Autism...American Occupational Therapy Association, INSPIRE Conference, March 31-April 3, 2022, San Antonio, Texas Congresses and Conferences/Texas - Hladik, Libby; Ausderau, Karla (American Journal of Occupational Therapy)
Date Presented 04/01/2022 The purpose of this project was to collaborate with stakeholders to develop evaluation tools to assess accessibility and inclusion of families with children with ASD in cultural institutions. A tool kit was developed in an iterative process through interviews, reviews of exhibits and visitor resources, and observations of programming to refine the utility of each specific tool. Six self-evaluation tools were developed to allow public institutions to self-assess their strengths and needs. Primary Author and Speaker: Libby Hladik Additional Authors and Speakers: Karla Ausderau